Violence in Buenaventura-Colombia: Reflections from the perspectives of Aníbal Quijano and Achille Mbembe - Acosta-Oidor, Catalina; Ortiz-Piedrahita, Vanessa (Sociedad y Economía, 2022)
This article aims to analyze the violent dynamics present in Buenaventura-Colombia, as part of the necropolitics implemented by the State in which various illegal armed actors and their repertoires of action –terror and death– are established as means to control the population. This analysis is conducted through the theoretical perspective of Aníbal Quijano on "The coloniality of power" and the vision of Achile Mbembe on "Necropolitics". Methodologically, the inquiry used a qualitative approach based on the analysis of the newspaper El País, the portal Verdad Abierta and the reports for Development and Peace (INDEPAZ) during the years 2010-2019. It is concluded that the socio-political context of Buenaventura is a clear example of the relationship between modernity, terror and death, due to a system of domination in which the ethnic- racial and social class classification of its inhabitants converge.